(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
The present article aims at illustrating methodologies, objectives and results of the ASIt project (Atlante Sintattico d’Italia) by focusing on the morphosyntax of expletive subject clitics. With the term ‘expletive subject clitics’ I will refer to unstressed pronouns which, in some northern vernaculars, occur with impersonal verbs (e.g. weather verbs, bisognare ‘it is necessary to’, sembrare ‘it seems that’) or with a postverbal subject as in existential or passive-si/se constructions. This contribution aims to verify Renzi & Vanelli’s 1983 generalizations regarding the distribution of expletive clitics on the basis of a larger database and draw some geo-linguistic considerations. KEYWORDS: syntax, clitics, Northern Italian dialects, expletive subject, impersonal verbs